Avaliação dos métodos de cálculos de iluminação natural através de aberturas zenitais - Andrade, Márcia Susana Stürmer de (2004)
This paper analyzes and evaluates the different results of calculus methods of natural illumination forecast in relation to measurement values through a zenithal opening and shows the adopted methodology when using small study models for carrying out such measurements. The comparative analysis of these results shows it validates the improvements and contributions proposed to the methods of the Daylight Coefficient (DC). The paper also presents a study on natural illumination and zenithal openings. Key words: calculus methods, zenithal openings, illumination, daylight coefficient.